2021
DOI: 10.1002/hsr2.327
|View full text |Cite
|
Sign up to set email alerts
|

The effects of genetic polymorphisms on benzene‐exposed workers: A systematic review

Abstract: Background and Aims Benzene is a group I carcinogen, which has been associated with leukemia and myelodysplastic syndrome. Moreover, it has been proposed that polymorphisms in benzene metabolizing genes influence the outcomes of benzene exposure in the human body. This systematic review aims to elucidate the existent relationship between genetic polymorphisms and the risk of developing adverse health effects in benzene‐exposed workers. Methods Three databases were syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In addition, studies have shown that benzene is genotoxic and can induce DNA damage and chromosome changes. Specific cytogenetic changes, including aneuploidy, chromosome translocation, and various other structural chromosome changes, have also been observed in people exposed to benzene ( 33 - 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies have shown that benzene is genotoxic and can induce DNA damage and chromosome changes. Specific cytogenetic changes, including aneuploidy, chromosome translocation, and various other structural chromosome changes, have also been observed in people exposed to benzene ( 33 - 35 ).…”
Section: Discussionmentioning
confidence: 99%